«La sana critica». Pubblicare i classici italiani nella Milano di primo Ottocento - Cadioli, Alberto (Moderna/Comparata, 2021)
In the early 19th-century, Milan was the most active Italian city in the publishing of books. There, collectors, librarians, scholars of ancient literature and young men of letters were protagonists in an intense activity of publishing classical texts. New editions of Divina Commedia, Petrarch's Rime, Boccaccio's Decameron, Ariosto's Orlando Furioso, Tasso's Gerusalemme Liberata and of many works by writers of the 18th century were published in Milan, in particular by Società Tipografica de' Classici Italiani (Italian Classical Writers' Printing Society). In a period rich in cultural and linguistic debates, even discussions on the procedures for publishing texts took on a new importance. By analysing the statements of the editors, investigating their textual choices, following their polemics, Alberto Cadioli, one of the well-known Italian textual bibliography scholars for the modern texts, underlines the importance of the «sana critica», the «sound criticism» - i.e. the philological practice, according to the language of that time - with which classical texts were published in Milan in the first decades of the 19th century. This book, that offers unknown data and a large documentation, reveals theoretical unexpectedly Modern observations and methodological indications, hidden in pages forgotten for many years.